2018
DOI: 10.4235/agmr.2018.22.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Frailty Index and FRAIL-NH Scale for the Assessment of the Frailty Status of Elderly Individuals Admitted in a Long-term Care Hospital in Korea

Abstract: Background Numerous elderly individuals with multimorbidity and impaired function are admitted in long-term care hospitals (LTCHs) in Korea. In this study, we aimed to describe the frailty status of elderly patients admitted in a LTCH using the FRAIL-NH scale and to identify the clinical relevance of frailty status on clinical outcomes, including death. Methods We retrospectively reviewed the medical records of 100 elderly patients who were hospitalized and died in an L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…In outcome prediction modelling, we used combined institutionalization due to functional decline and mortality as a major study outcome, because mortality alone was insufficient to produce statistically meaningful differences in analysis. However, as a study showing that chronic institutionalization occurs in older adults who are functionally dependent, and rather irreversible, resulting in death in initially admitted facilities, institutionalization might be considered as a major outcome of mortality. Also, the cohort study was based in a single rural region of Korea; therefore, generalization in the global population may be restricted.…”
Section: Discussionmentioning
confidence: 99%
“…In outcome prediction modelling, we used combined institutionalization due to functional decline and mortality as a major study outcome, because mortality alone was insufficient to produce statistically meaningful differences in analysis. However, as a study showing that chronic institutionalization occurs in older adults who are functionally dependent, and rather irreversible, resulting in death in initially admitted facilities, institutionalization might be considered as a major outcome of mortality. Also, the cohort study was based in a single rural region of Korea; therefore, generalization in the global population may be restricted.…”
Section: Discussionmentioning
confidence: 99%
“…FRAIL-NH score of 0–1 is robust, 2–6 pre-frail and 7 or above as frail [ 22 ]. The FRAIL-NH scale has been validated in Asians populations including Korea [ 23 ]. Locally, FRAIL has been compared to other frailty measurements such as the Clinical Frailty Scale and Tilburg Frailty Indicator, and has been found to be better at predicting in-hospital mortality and length of hospitalisation [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another explanation may be the high prevalence of frailty among LTCH patients who are more physically vulnerable compared to those in other nursing homes. 17 )…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation may be the high prevalence of frailty among LTCH patients who are more physically vulnerable compared to those in other nursing homes. 17) Rothan-Tondeur et al 16) reported bronchitis (35.5%) to be the most common type of HAI, followed by gastroenteritis (23.8%), UTI (16.7%), otorhinolaryngological infection (8.7%), and pneu- Values are presented as number (%) or mean±standard deviation. monia (7.0%).…”
Section: B)mentioning
confidence: 99%